PENDIDIKAN ISLAM DI NEGARA-NEGARA MELAYU MODERN (SINGAPURA, BRUNEI DARUSSALAM, DAN THAILAND SELATAN) - Jossiselfiah; Juli Kustanto; Ismail Sukardi; Nyayu Soraya (STKIP Subang, 2026)
Islamic education in the modern Malay region faces diverse challenges and developments influenced by the social, political, and policy contexts of each country. This study aims to analyze the development of Islamic education in Singapore, Brunei Darussalam, and Southern Thailand, as well as to identify their similarities and differences. The research employs a library research method with a descriptive qualitative approach through the examination of books, scholarly journals, scientific articles, and other relevant documents. The collected data were analyzed using content analysis to obtain a comprehensive understanding of Islamic education systems in the three regions. The findings reveal that Islamic education in Singapore is developed through a madrasa system integrated with the national education framework, while in Brunei Darussalam it receives strong state support under the philosophy of Malay Islamic Monarchy (Melayu Islam Beraja/MIB). In Southern Thailand, Islamic education plays a significant role in preserving Malay-Muslim identity amid national integration policies. These findings indicate that Islamic education functions not only as a medium for transmitting religious knowledge but also as an important instrument for shaping the Islamic identity of Muslim communities.